Lucien's gamble ebook - Day, Sylvia (2006)
Lucien's Gamble Lucien Remington's reputation as a debauched libertine who plays by no one's rules—in business or the bedroom—is well deserved. He gets what he wants, social repudiation be damned. But society can keep from him the one thing he truly desires, the untouchable Lady Julienne La Coeur. Until she sneaks into his club dressed as a man and searching for her irresponsible brother. Suddenly she's in Lucien's grasp, his to take, and his mind is filled with the most wickedly sinful thoughts. A gentleman would walk away from the temptation she presents. But then, Lucien has never claimed to be a gentleman. . .